Residual phosphorus effects and nitrogen x phosphorus interactions in soybeanmaize rotations on a Pdeficient Ferralsol - Vandamme, Elke; Pypers, Pieter; Vanlauwe, Bernard; Baijukya, Frederick P.; Smolders, E.; Merckx, Roel (Springer, 2014)
Legume-cereal rotations are an essentialcomponent of integrated soil fertility management inlow-input cropping systems, but strategies are needed toincrease phosphorus (P) fertilizer use efficiency in suchsystems. These may include preferential targeting of Pto one of the crops in the rotation cycle, the use ofP-efficient genotypes, and the optimization of the ratesof P fertilizer used. A field trial was conducted toevaluate the effects of increasing P fertilizer rates (0, 11,22 and 44 kg P ha-1, added as triple super phosphate)applied to three soybean genotypes grown on a P-deficientFerralsol, on the nitrogen (N) and P nutrition of asubsequent maize crop. In addition, a greenhouse trialwas set up to assess N, P and other rotation effects ofthree soybean genotypes on a subsequent maize croprelative to a maize–maize rotation at high and low Psupply. In the field trial, soybean did not respond toincreasing P rates, but residual P effects improvedmaizegrain yields by up to 90 %.Ear leaf (field trial) and shoot(pot trial) P concentrations increased by applying N tomaize, demonstrating important N 9 P interactions.The pot trial did not reveal a positive rotation effect ofsoybean on maize beyond the mere N-benefit, showingthat soybean was not able to improve P availability tomaize after correcting for the N-effect. No variation inrotation effects onmaize among soybean genotypes wasobserved. Because of the absence of effects of thesoybean crop on P availability to maize, opportunities toincrease P fertilizer use efficiency in soybean–maizerotations mainly reside in maximizing P uptake by eachcrop separately and in matching P fertilizer rates withcrop demand.